Effect of Problem Based Learning and Lecture Based Learning on Nursing Students at Oman Nursing Institute - Rajha A. Hamza (Kufa Journal for Nursing Sciences)
Background: As this study was conducted by using a new strategy for the first time at Oman Nursing Institute, as one of the institutes that works under the umbrella of Directorate General Education & Training DGET at Ministry of health in Oman. Using of the teaching methods that provide matching between theory and clinical have a vital role in improve the students educational level.